LIPID AND GLYCEMIC PROFILE OF RATS FED ON DIETS WITH BANANA PEEL AND BANANA STALK - Thielen Borba da Costa; Catia Silva Silveira; Marina Couto Pereira; Elizabete Helbig (Universidade do Estado do Rio de Janeiro, 2018)
Objective: The aim of this study was to evaluate the effects of dietary intake of fiber present in banana peel and stalk on the blood glucose and lipid profiles of Wistar rats. Methodology: This research was conducted for 65 days to study the influence of diets containing fiber from banana peel (PGF), banana stalks (SFG) and both types of fiber (PSFG), as compared with the control diet (CG), on the glycemic and lipid profile of 24 male Wistar rats, with a mean initial weight of 54.06 g, distributed equally into four groups. The control group (CG) received the AIN diet plus 1% crystalline cholesterol and 0.1% colic acid and the experimental diets were similar to the control group, except for substitution of the fiber source. Results: In the treatment groups (PFG, SFG and PSFG), there was an increase in glycemic, triglyceride and serum total cholesterol and LDL-C levels compared with the control group (CG). The levels of VLDL-C were reduced only in the group containing fibers from the peel. Conclusions: Inclusion of dietary fiber from banana peels and stalks, as well as the mixture of both types of fiber, showed effectiveness of use on the lipid profile and the ability to maintain the blood glucose levels of rats fed on diets containing fiber from the peel and the stalk. DOI: 10.12957/demetra.2018.29559